Simplify 911z − 411z

9
11
𝑧



4
11
𝑧
.(1 point)

1 answer

To simplify the expression \( 911z - 411z \), we can combine like terms. Both terms contain the variable \( z \).

Here's how it works step by step:

\[ 911z - 411z = (911 - 411)z \]

Now, we subtract 411 from 911:

\[ 911 - 411 = 500 \]

So, we can rewrite the expression as:

\[ 500z \]

Thus, the simplified expression is:

\[ \boxed{500z} \]

Similar Questions
  1. simplifying square roots1) find volume of this prism? v=bwh b=√12" w=√6" h=√8" 2)simplify: √576 3)simplify: √400
    1. answers icon 3 answers
  2. Simplify 8a − 2a.Simplify 12e − 5f − 7e +3f. Simplify 9x + 3y − 6 − 5x + 4y −3. Simplify 9/11z − 4/11z. Simplify
    1. answers icon 4 answers
  3. simplifying square roots1) find volume of this prism? v=bwh b=√12" w=√6" h=√8" 2)simplify: √576 3)simplify: √400
    1. answers icon 3 answers
  4. So I need some help on these Graphing Square Root Functions Quiz questions.1. Simplify 2 over √5 2. Simplify -11√112 3.
    1. answers icon 1 answer
more similar questions